Update: Antarctic Winterover as an Analog for Spaceflight Immune Dysregulation - Makedonas, George; Pierson, Duane L.; Crucian, Brian E.; Basner, Mathias; Mehta, Satish K.; Krieger, Stephanie S.; Stahn, Alexnder; Chouker, Alexander (2019)
Orbital spaceflight perturbs the human immune system significantly; Natural Killer (NK) and T-lymphocyte (T) cell functions are most susceptible to spaceflight-induced impairment. This loss of function may manifest in persistent latent virus reactivation (CMV, EBV, VZV), which does occur at a higher frequency in astronauts compared to earthlings.